The role of proximal-enhancer elements in the glucocorticoid regulation of carbamoylphosphate synthetase gene transcription from the upstream response unit - Schoneveld, Onard J.L.M.; Gaemers, Ingrid C.; Hoogenkamp, Maarten; Lamers, Wouter H. (Biochimie, 2005)
As part of the urea cycle, carbamoylphosphate synthetase (CPS) converts toxic ammonia resulting from amino-acid catabolism into urea. Liver-specific and glucocorticoid-dependent expression of the gene involves a distal enhancer, a promoter-proximal enhancer, and the minimal promoter itself. When challenged with glucocorticoids, the glucocorticoid-responsive unit (GRU) in the distal enhancer of the carbamoylphosphate-synthetase gene can only activate gene expression if, in addition to the minimal promoter, the proximal enhancer is present. Here, we identify and characterise two elements in the proximal CPS enhancer that are involved in glucocorticoid-dependent gene activation mediated by the GRU. A purine-rich stretch forming a so-called GAGA-box and a glucocorticoid-response element (GRE) are both crucial for the efficacy of the GRU and appear to constitute a promoter-proximal response unit that activates the promoter. The glucocorticoid response of the CPS gene is, therefore, dependent on the combined action of a distal and a promoter-proximal response unit.